Dosis de probiótico en las características agronómicas y rendimiento del forraje verde hidropónico de Zea mays L. Iquitos, Loreto - Diaz Torres, Ericka Magaly (2024)
The research evaluated the impact of different doses of probiotics on the agronomic characteristics and yield of hydroponic green corn forage (Zea mays) in Zúngarococha, during 2023. Using an experimental design, five treatments with different concentrations of probiotics were applied and parameters such as plant height, stem diameter, number of leaves, and fresh and dry matter yields were measured. The data collected were statistically analyzed using the "R Study" program. The results showed that probiotic doses significantly influenced most of the agronomic traits evaluated. An optimal dose that maximizes both forage growth and yield was identified, suggesting that the proper use of probiotics can improve productivity in hydroponic culture systems. In addition, the study highlights the importance of precise handling of probiotics to avoid negative effects associated with excessive doses. These results contribute to the knowledge about the management of probiotics in the production of hydroponic forage, offering guidelines to optimize crop yield under controlled conditions. The research provides a basis for future explorations on the application of probiotics in different agricultural contexts, underscoring their potential to improve the efficiency and sustainability of agricultural production in tropical regions.